Outcomes and Complications of Ahmed Tube Implantation in Asian Eyes. Issue 8 (August 2018) - Choo, Jessica Q.H.; Chen, Z.D.; Koh, Victor; Liang, Shen; Aquino, Cecilia M.; Sng, Chelvin; Chew, Paul
Abstract : Purpose: There is a lack of long-term Asian studies on the efficacy and safety of Ahmed glaucoma valve (AGV) implantation. This study seeks to determine the outcomes and complications of AGV implantation in Asians. Methods: A retrospective review of AGV surgeries performed at a single center in Singapore was conducted. A total of 76 patients with primary and secondary glaucoma who underwent their first AGV surgery from January 1, 2010 to December 31, 2012 were considered for our study. Primary outcomes evaluated were as follows: failure, intraocular pressure, best-corrected visual acuity, number of intraocular pressure (IOP)-lowering medications, and complications. Failure was defined by the following: IOP >21 mm Hg on 2 consecutive visits after 3 months, IOP⩽5 mm Hg on 2 consecutive visits after 3 months, reoperation for glaucoma, removal of implant, or loss of light perception vision. Results: Mean follow-up duration was 33.2±6.9 months. There was significant reduction in IOP (mean reduction, 25.9%; P <0.001) and number of IOP-lowering medications (mean reduction, 77.8%; P <0.001) at 3 years. Absolute failure rate was 23.9% at 3 years with no difference between eyes with or without previous trabeculectomy and between eyes with primary or secondary glaucoma. Occurrence of postoperative hyphema was a significant risk factor for failure. The commonest postoperative complications were hyphema and tube exposure. Conclusions: At 3 years after AGV surgery in Asian eyes, less than one-quarter of the eyes fulfilled the criteria for surgical failure.